Neuronal Cell Differentiation of Human Dental Pulp Stem Cells on Synthetic Polymeric Surfaces Coated With ECM Proteins - Gao, Yan; Tian, Zeyu; Liu, Qian; Wang, Ting; Ban, Lee-Kiat; Lee, Henry Hsin-Chung; Umezawa, Akihiro; Almansour, Abdulrahman I.; Arumugam, Natarajan; Kumar, Raju Suresh; Ye, Qingsong; Higuchi, Akon; et al. (Frontiers in Cell and Developmental Biology, 2022)
Stem cells serve as an ideal source of tissue regeneration therapy because of their high stemness properties and regenerative activities. Mesenchymal stem cells (MSCs) are considered an excellent source of stem cell therapy because MSCs can be easily obtained without ethical concern and can differentiate into most types of cells in the human body. We prepared cell culture materials combined with synthetic polymeric materials of poly-N-isopropylacrylamide-co-butyl acrylate (PN) and extracellular matrix proteins to investigate the effect of cell culture biomaterials on the differentiation of dental pulp stem cells (DPSCs) into neuronal cells. The DPSCs cultured on poly-L-ornithine (PLO)-coated (TPS-PLO) plates and PLO and PN-coated (TPS-PLO-PN) plates showed excellent neuronal marker (βIII-tubulin and nestin) expression and the highest expansion rate among the culture plates investigated in this study. This result suggests that the TPS-PLO and TPS-PN-PLO plates maintained stable DPSCs proliferation and had good capabilities of differentiating into neuronal cells. TPS-PLO and TPS-PN-PLO plates may have high potentials as cell culture biomaterials for the differentiation of MSCs into several neural cells, such as cells in the central nervous system, retinal cells, retinal organoids and oligodendrocytes, which will expand the sources of cells for stem cell therapies in the future.